2014
DOI: 10.1200/jco.2013.54.4577
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival After Transplantation of More Donor Plasmacytoid Dendritic or Naïve T Cells From Unrelated-Donor Marrow Grafts: Results From BMTCTN 0201

Abstract: A B S T R A C T PurposeTo characterize relationships between specific immune cell subsets in bone marrow (BM) or granulocyte colony-stimulating factor-mobilized peripheral blood (PB) stem cells collected from unrelated donors and clinical outcomes of patients undergoing transplantation in BMTCTN 0201. Patients and MethodsFresh aliquots of 161 BM and 147 PB stem-cell allografts from North American donors randomly assigned to donate BM or PB stem cells and numbers of transplanted cells were correlated with overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 30 publications
6
97
3
1
Order By: Relevance
“…5 The absence of impact of CD8 1 T cells in our study is probably explained by the use of ATG for in vivo T-cell depletion in the majority of patients, whereas no T-cell depletion was performed in the study of Reshef et al Of note, Waller et al did not identify a PBSC graft cell subset significantly associated with patient outcome 10 ; however, the impact on the GPFS composite end point was not evaluated in that study. Of note, one could speculate that iNKT frequencies might represent a surrogate for some favorable combination of other subset.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…5 The absence of impact of CD8 1 T cells in our study is probably explained by the use of ATG for in vivo T-cell depletion in the majority of patients, whereas no T-cell depletion was performed in the study of Reshef et al Of note, Waller et al did not identify a PBSC graft cell subset significantly associated with patient outcome 10 ; however, the impact on the GPFS composite end point was not evaluated in that study. Of note, one could speculate that iNKT frequencies might represent a surrogate for some favorable combination of other subset.…”
Section: Discussioncontrasting
confidence: 40%
“…9 The only report on a large collection of immune subsets failed to demonstrate an association between donor immune cells in the PBSC graft and the SCT outcome, 10 whereas bone marrow grafts with more naïve T cells and plasmacytoid dendritic cells were associated with an improved survival. 10 Furthermore, in these studies, improved outcome associated with graft cell subsets was linked to either a decreased incidence of relapse 5 or a decreased incidence of GVHD. 6 However, although 1 graft cell subset can contribute to reduce GVHD, it may also reduce GVT and therefore increase the relapse risk.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] The majority of RIC transplantations use mobilized PBSC grafts that contain 10 10 to 10 11 T cells, the primary mediators of the immunologic graft-versus-host and graft-versus-tumor (GVT) responses. Because the curative potential of RIC transplantation relies entirely on a potent GVT effect, T-cell doses and their subsets may be critical.…”
Section: Introductionmentioning
confidence: 99%
“…49 Further, Waller et al 50 recently found an association between the number of pDCs within BM graft and OS, but failed to show any correlation between pDCs in PBSC and outcome or GVHD.…”
Section: Mobilized Pbsc: the Immunological Perspective F Saraceni Et Almentioning
confidence: 99%